2022
DOI: 10.1101/2022.11.05.515274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipocyte lipolysis protects the host againstTrypanosoma bruceiinfection

Abstract: Trypanosoma brucei, an etiological agent of African trypanosomiasis, colonizes the interstitial spaces of the adipose tissue in disproportionately high numbers, inducing a robust local immune response. Loss of body weight, including loss of adipose mass, is a hallmark symptom of African trypanosomiasis. Nevertheless, it is unclear which molecular mechanisms drive this loss of adipose mass and in turn whether it contributes to pathology. Here we show that lipolysis is activated early in infection in adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…PCF parasites respond by scavenging large amount FA sources from the serum, if in high-fat media, or by reducing the ratio of C22/C20 PUFAs, if in low-fat media, to maintain the membrane homeostasis and rescue their growth. We also found that, in keeping with recent studies by Machado et al, (39) some environmental PUFAs, can have a detrimental effect on the parasite cell growth, like shown for WT and Δ6-KD PCF under DHA supplementation. Despite that, WT and Δ6-KD PCF cells showed the typical full range of cellular FA species, where an increase of C18:0/C18:1 and C18:2 ratio was observed to ensure once again membrane homeostasis and cell survival.…”
Section: Discussionsupporting
confidence: 92%
“…PCF parasites respond by scavenging large amount FA sources from the serum, if in high-fat media, or by reducing the ratio of C22/C20 PUFAs, if in low-fat media, to maintain the membrane homeostasis and rescue their growth. We also found that, in keeping with recent studies by Machado et al, (39) some environmental PUFAs, can have a detrimental effect on the parasite cell growth, like shown for WT and Δ6-KD PCF under DHA supplementation. Despite that, WT and Δ6-KD PCF cells showed the typical full range of cellular FA species, where an increase of C18:0/C18:1 and C18:2 ratio was observed to ensure once again membrane homeostasis and cell survival.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we propose a model whereby subcutaneous adipocytes (in addition to Langerhans cells and keratinocytes) have a critical role as coordinators of local innate and adaptive immune responses. In the context of trypanosome infection, subcutaneous adipocytes may detect the presence of parasites (e.g., via Toll-like receptor signalling) to trigger the recruitment and activation of innate immune cells such as gd T cells to mobilise energy stores to meet the energetic requirements needed to control infection, as recently proposed 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in response to our third question, we found that both, lymph nodes and the lymphatic vasculature are highly remodeled throughout infection. While we have shown that remodeling of equivalent nature occurs in other organs (De Niz et al, 2021;Machado et al, 2022;Trindade et al, 2016), it is important to consider the implications of lymphatic system compromise. Although T. brucei is not considered per se a lymphatic disease as lymphatic filariasis is, it induces remarkable changes in systemic homeostasis as shown by the presence of major oedema (composed of heavily parasitized fluid) throughout the whole mouse body.…”
Section: Discussionmentioning
confidence: 96%